STRATEGI KOMUNIKASI PEMASARAN OPPO BENGKULU “Studi Deskriptif TSPV dalam Berkomunikasi dengan Promotor OPPO Cabang Bengkulu” - Putri Ning Rahayu (UNIVED PRESS, Universitas Dehasen Bengkulu, 2020)
Marketing Communication is a form of strategy intended to improve the quality of the company and the limited company's goals. In addition, marketing communication activities are activities that are designed to create structured management and reach the quality of work in company. The research was conducted to find out how the Marketing Communication Strategy for marketing activities in the OPPO Bengkulu Company. The object of this study was carried out to study marketing strategies in marketing activities at the OPPO Bengkulu company. While the research subjects were the OPPO Bengkulu Company which was stationed in Bengkulu and chosen by this company because of its position as TSPV manager in the field of discussing and improving the quality of the company (promoter). The theory used in this research is the theory of Internal Communication according to Lawrence D. Brennan which supports two things, namely vertical and horizontal communication. The research has revealed the marketing process itself by establishing a feed on activities as well as the marketing process. The results showed that team management and knowledge control were very important in increasing sales and customer satisfaction found in the case study. Based on the analysis, it is concluded that the marketing communication strategy of OPPO Bengkulu company uses the activities of the TSPV management team consisting of training products, follow-up, persuasive communication and impact management. Many marketing activities are supported by TSPV team activities towards promoters (employees) in increasing sales figures. Keywords : strategy, marketing communication, marketing activities.